2015
DOI: 10.1007/jhep04(2015)118
|View full text |Cite
|
Sign up to set email alerts
|

Background independent exact renormalization group for conformally reduced gravity

Abstract: Within the conformally reduced gravity model, where the metric is parametrised by a function f (φ) of the conformal factor φ, we keep dependence on both the background and fluctuation fields, to local potential approximation and O(∂ 2 ) respectively, making no other approximation. Explicit appearances of the background metric are then dictated by realising a remnant diffeomorphism invariance. The standard non-perturbative Renormalization Group (RG) scale k is inherently background dependent, which we show in g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(136 citation statements)
references
References 58 publications
(207 reference statements)
8
127
1
Order By: Relevance
“…Starting from the flow equation derived in [24], the existence of fixed functions f * (R) have been investigated by various groups in d = 3 [53][54][55] and d = 4 [56][57][58][59][60] spacetime dimensions. Quite unsettling, the verification of a suitable NGFP at the level of fixed functions turned out to be extremely challenging: while the finite-dimensional computations always produced a suitable UV fixed point regardless of the computational details and setting, up to now the fixed function completing the four-dimensional NGFP in the ansatz (1.2) is still elusive.…”
Section: From Fixed Points To Fixed Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the flow equation derived in [24], the existence of fixed functions f * (R) have been investigated by various groups in d = 3 [53][54][55] and d = 4 [56][57][58][59][60] spacetime dimensions. Quite unsettling, the verification of a suitable NGFP at the level of fixed functions turned out to be extremely challenging: while the finite-dimensional computations always produced a suitable UV fixed point regardless of the computational details and setting, up to now the fixed function completing the four-dimensional NGFP in the ansatz (1.2) is still elusive.…”
Section: From Fixed Points To Fixed Functionsmentioning
confidence: 99%
“…At this stage it is unclear whether all principles are strictly necessary for establishing a suitable fixed function. In particular, the list does not incorporate the recent observation [60,63] that the combination of a flow equation with the equation for the modified split Ward identities may lead to substantial simplifications of the PDEs prescribing the fixed functions of the theory.…”
Section: Jhep08(2015)113mentioning
confidence: 99%
“…However this is also an area where there is little guidance from current experimental observation or other techniques, and therefore one must place particular reliance on a rigorous understanding of the mathematical structure that the exact RG exposes, in so far as this is possible. This is especially so with recent work on "functional truncations" [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…But this has to begin by building on a thorough understanding of what is legitimate in a well-understood situation such as that of scalar field theory. Moreover, recent work has shown that, despite the complications induced by diffeomorphism invariance and background independence [18,20,37], the overall scalar factor part of the metric (at least within the so-called conformal truncation) has RG properties that are just those of a scalar field theory -but crucially with wrong sign kinetic term [28,36]. Furthermore this one sign profoundly alters the RG properties (unless the field is continued to the imaginary axis) [36].…”
Section: Introductionmentioning
confidence: 99%
“…[2], there is a wealth of literature investigating asymptotic safety in this way. For reviews and introductions see [10][11][12][13][14], and for recent advances see for example [15][16][17][18][19][20][21][22][23][24]. In the vast majority of this work the RG flow equation takes the generic form [3]:…”
Section: Introductionmentioning
confidence: 99%